Information, Communication and Society - Neelameghan, A. (Journal of Information and Knowledge, 1980)
Define the concepts Information, Communication and 'Society'. Indicates the interrelation of these concepts in the field of information science and service. The time-binding nature of communication and the evolution of societal homeostasis are discussed. The factors affecting communication and the environmental effect of information technology are highlighted.